Educational Inequality among Street Children in Metropolitan India: Assessing the Impact of NEP 2020 - Kapil, Dev (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This paper critically investigates educational inequality among street children in major metropolitan centers of India, focusing on the effects of the National Education Policy (NEP) 2020. Through qualitative and quantitative analysis—including interviews with urban street children and data from non-governmental organizations—the research highlights persistent barriers to educational access, compounded by socio-economic precarity and urban displacement. Although NEP 2020 aspires for universal and inclusive education, its rapid push towards digital learning has inadvertently exacerbated the digital divide among street children, who lack devices, connectivity, and stable learning environments. The study finds that new digital platforms and flexible curriculum models have had limited reach without comprehensive social support and grassroots outreach. The research concludes that true educational inclusion for metropolitan street children requires not only digital solutions but also dedicated policy interventions addressing basic welfare, community-based educational outreach, and access to physical and psychological support systems. These findings call for a nuanced, multi-sectoral effort to realize the inclusive aims of NEP 2020 for India’s most marginalized urban youth.